Impact of atmospheric pressure DBD plasma treatment on the biodegradability, hydrophilicity, and mechanical properties of PVA/PEG/Chitosan/HA nanofibers for bone tissue engineering - Hartatiek; M.I. Wuriantika; Yudyanto; A. Taufiq; M. Diantoro; Y. Yusuf; M. Taufik; J.F. Fatriansyah (Talanta Open)
The effectiveness of scaffolds in supporting bone tissue regeneration is highly dependent on surface modification. Atmospheric pressure dielectric barrier (DBD) plasma treatment offers a practical method that offers simplicity, time efficiency, cost effectiveness, and reliable results. In this study, nanofiber scaffolds composed of PVA, PEG, chitosan, and hydroxyapatite were fabricated using electrospinning and treated with DBD plasma at varying distances. Optical emission spectroscopy (OES) confirmed the presence of reactive species such as OH radicals, nitrogen (N2), and nitrogen ions (N2+). These species caused changes in surface morphology, including an increase in fiber diameter. These surface morphological modifications were associated with mechanical properties and hydrophilicity. Furthermore, scaffolds treated at a distance of 1.5 mm showed a degradation rate of up to 70 % after three weeks. The results highlight the potential of DBD plasma treatment to optimize the performance of bone tissue engineering scaffolds.